Pelatihan Penggunaan Aplikasi Mendeley Pada Mata Kuliah Kajian Penulisan Artikel Dan Publikasi Menggunakan Buku Panduan Mendeley Di Pendidikan Sejarah Universitas Riau - Afrillyan Dwi Syahputra, Muhammad; Fikri, Asyrul; Perwira Negara, Chandra; Warsani, Henki; Ramona, Nadia; Wahyuni, Anny (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
The Article Writing and Publication Study course is one of the elective courses taken by History Education students at the University of Riau. This course aims to provide students with competencies in terms of mastering the theory and practice of writing scientific articles and their publications. This includes theoretical understanding, publication analysis, writing skills, publication strategies, mastery of technology, and application of ethics in writing scientific papers. The low understanding of citations and reference list management is the main problem in compiling this guidebook. The purpose of making this guidebook is as a medium to facilitate students in working on reports, articles, and even theses that must use Mendeley in their citation management. Determination of issues is obtained from the results of discussions with the Head of Department, Study Program Coordinator, and Lecturers. Determination of priority issues uses the USG method (Urgency, Seriousness, Growth). The result of this activity is the formation of a draft of the Mendeley Usage Guidebook. The book consists of 6 main topics, namely Mendeley History, Mendeley installation, connecting Mendeley to Microsoft Word, adding references, adding citations, and adding Bibliography (bibliography). As a complement, a guidebook is also attached in the form of an e-Book that is directly connected to the GDrive link, so that students can download the guidebook in the form of a QR Code.